Lipskian analysis of child protection failures from Victoria Climbie to 'baby p': A street-level re-evaluation of Governance - Marinetto, Michael (2011)
This paper explores the issue of joined-up governance by considering child protection failures, firstly, the case of Victoria Climbie who was killed by her guardians despite being known as at risk child by various public agencies. The seeming inability of the child protection system to prevent Victoria Climbie's death resulted in a public inquiry under the chairmanship of Lord Laming. The Laming report of 2003 looked, in part, to the lack of joined-up working between agencies to explain this failure to intervene and made a number of recommendations to improve joined-up governance. Using evidence from detailed testimonies given by key personnel during the Laming Inquiry, the argument of this paper is that we cannot focus exclusively on formal structures or decision-making processes but must also consider the normal, daily an informal routines of professional workers. These very same routines may inadvertently culminare in the sort of systematic failures that lead to child protection tragedies. Analysis of the micro-world inhabited by professional workers would benefit most, it is argued here, from the policy-based concept of street-level bureaucracy developed by Micheal Lipsky some 30 years ago. The latter half of the paper consider child protection failures that emerged after the Laming-inspired reforms. In particular, the case of 'Baby P' highlights, once again, how the working practices of street-level professionals, rather than a lack of joined-up systems, may possibly complement an anlysis of, and help us to explain, failures in the child protection system. A Lipskian analysis generally offers, although there are some caveats, only pessimistic conclusions about the pospects of governing authoriteis being able to avoid future child protection disasters. These conclusions are not wholeheartedly accepted. There exists a glimmer of optimism because street-level bureaucrats still remain accountable, but not neccessarily in terms of top-down relations of authority rather, in terms of interpersonal forms of accountability - accountability to professionals and citizen consumers of services. - Reproduced.
Keywords: Child welfare